Scope of general purpose financial reporting: an accountability perspective - Jorge, Susana (2021)
It has been discussed in the public sector accounting literature that one of the common reasons given for the adoption of accrual accounting in the public sector is the discharge of accountability. However, there is argument in the literature, which strongly debates whether the requirement for public sector entities to provide financial statements based on private sector GAAP impacts positively or negatively on public sector accountability outcomes. The discharge of accountability obligations requires the provision of information about the entity’s management of resources entrusted to it for the delivery of services to constituents and others. Given the way in which the services provided by public sector entities are funded (primarily by taxation revenues or other non-exchange transactions) and the dependency of service recipients on the provision of those services over the long term, the discharge of accountability obligations will also require the provision of information about such matters as the entity’s service delivery achievements during the reporting period, and its capacity to continue to provide services in future periods. Accordingly, accountability of public sector organizations must embrace both financial and non-financial information on the use of resources and services performed and the ways in which organizations contribute to the creation of value for stakeholders, namely the impact of their public service provision on society. Moreover, this information must be understandable by all stakeholders, and especially by non-expert citizens, particularly addressed in a democratic accountability process. Public sector organizations have tried to develop several types of reports to consider these issues. Subsequently, this chapter deals with discharge of accountability by public sector entities, addressing different reporting perspectives, complementing that of financial reporting.